Perspectives of Parents on Communication Challenges Faced in Educating Learners with Hearing Impairments - and Ogada, Rosemary (2019)
Focusing on Education Policy for Deaf Children, the World Federation of the Deaf (WFD, 2016) postulated that children with HI have a right to full access to quality education and that since persons with hearing impairments (HI) are mainly visual, sign language and visual strategies must be availed to learners with HI as a birthright. This may be interpreted to mean that if quality education is not availed to learners with HI using visual strategies and in sign language, the policies laid down by WFD would have been contravened. It can also be implied that sign language needs to be availed to learners with HI at home with parents, siblings and care givers where they grow and learn before going to school. The purpose of this study was therefore to establish the perspectives of parents on communication challenges faced in educating learners with hearing impairments in. This study adopted a case study research design using a qualitative research approach and was informed by the Social Model of Disability as propagated by Union of Physically Impaired Against Segregation (UPIAS) (1976). The objective of the study was to establish the perspectives of parents on communication challenges faced in educating learners with hearing impairments. The target population was 177 comprising 150 parents of learners with hearing impairments, 26 teachers and 1 Quality Assurance and Standards Officer. The study employed purposive sampling technique to sample 30 parents and 13 teachers while saturated sampling technique was used to for 1 Quality Assurance and Standards Officer (QUASO). Data was collected by use of interview schedules, focus group discussion guides and document analysis guides. Trustworthiness was established by use of detailed report of the process within the study, member checks and overlapping methods. Data was analyzed using thematic analysis technique as proposed by Braun and Clarke (2006). The study established that most parents of learners with hearing impairments held the view that sign language was too difficult to learn at their age though they expected the school and the government to facilitate sign language trainings for them. This study concluded that communication between parents and their children was ineffective because parents viewed themselves as unable to learn sign language and communication between parents and the school was ineffective because most parents viewed the teachers as disorganized in the way they communicated with parents. Keywords: Hearing impairments, communication, parents, learners, challenges, educating learners with HI DOI : 10.7176/JEP/10-3-04